A Retrospective Analysis Comparing Technical Difficulty and Safety between Right and Left-sided Percutaneous Transhepatic Biliary Drainage in a Nondilated Biliary System - Ranjan Kumar Patel; Taraprasad Tripathy; Bramhadatta Pattnaik; Tanmay Dutta; Sunita Gupta; Hemant Kumar Nayak; Manas Kumar Panigrahi; Deepak Das; Sandip Kumar Barik; Sudipta Mohakud; Suprava Naik; Nerbadyswari Deep Bag (Indian Journal of Radiology and Imaging)
Objective The aim of this study was to compare the technical difficulty and safety between right-sided percutaneous transhepatic biliary drainage (R-PTBD) and left-sided percutaneous transhepatic biliary drainage (L-PTBD) in patients with nondilated bile ducts.